Glycemic Control and Sleep Hygiene: Investigating their Association Among Type 2 Diabetes Patients in Primary Care - Gomez Garduño, Floriberto; Garfias-López, Ana Karen; Bernal-Silva, Sofía; Comas-García, Andreu (British Journal of Healthcare and Medical Research, 2025)
Background: Diabetes, a metabolic disorder, mainly involves chronic hyperglycemia. Sleep is a reversible state of inactivity associated with a reduced response to the external environment. Good sleep hygiene, an environment, and daily routines that promote consistent, uninterrupted sleep. There is evidence that links sleep to metabolic responses. Methods: Quantitative case-control study, longitudinal, retrospective, observational. 126 questionnaires, including the Sleep Hygiene Index and the recollection of data survey for this study, were applied to adult diabetic patients who came for consultation at the CADIMSS program in the Family Medicine Unit No. 47 in San Luis Potosí, from August to December 2023. Results: Inadequate glycemic control in type 2 diabetic patients was associated with poor sleep hygiene, with a treatment-adjusted odds ratio of 44.64. Half of the patients do not comply with the exercise regime, and two out of three do not follow the dietary regime. The most frequently used treatments in cases are insulin and SGLT-2 inhibitors. On the other hand, controls were treated with metformin. The number of hours slept was not different in both groups. Conclusions: Inadequate glycemic control in type 2 diabetic patients treated at CADIMSS was associated with poor sleep hygiene.